EMERGING TRENDS OF PUBLIC ADMINISTRATION AND THEIR IMPACT ON SOCIO-ECONOMIC DEVELOPMENT - Sarfraz Batool, Shahbaz Ali Khan, Arsalan Rasool (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Many experts of developmental studies are convinced that effective public administration is a good tool for socio-economic and political development at the national, regional, and international levels. However, the conventional style of public administration is unable to cope with the needs and challenges of development in the age of liberal economic order. Major reforms have been done in the structures of public administration worldwide to make it vibrant and efficient to boost up the process of development at the local, regional and global level. However, there is a dire need for the digitalization of public administration to raise global economic conductivity. This paper discusses three major points: first how public administration is linked with socio-economic development? Second, why reforms are needed in the structure, procedure, and practice of public administration in the era of modern development? Finally, how the latest trend of digital public administration can serve as an effective tool for socio-economic development in the globalized world? The paper finds that after the digitalization of public administration, the process of socio-economic development will be accelerated in the globalized world due to efficient and transparent public service delivery.